Janus Surface Micelles on Silica Particles: Synthesis and Application in Enzyme Immobilization. Issue 4 (18th February 2021) - Wang, Huan; Hou, Wangmeng; Liu, Yingze; Liu, Li; Zhao, Hanying
Abstract : Front Cover : Enzyme immobilization can optimize the performance of the immobilized enzymes. An ideal immobilization system must offer protection to the immobilized enzyme with retained bioactivity. In article number 2000589 by Hanying Zhao and co‐workers, Janus surface micelles (JSMs) are fabricated on the silica particles by polymerization induced surface self‐assembly process. It is demonstrated that JSMs can be used as an ideal platform for the immobilization of enzymes.